Blue Accounting dalam Perspektif Teori Legitimasi dan Stakeholder - Pratama, Diandra Ayu (Jurnal KIAFE, 2025)
The increase in economic activities in the maritime sector has driven the need for better accountability in marine resource management, known as Blue Accounting. This research aims to explore the concept of Blue Accounting within the framework of Blue Economy development in Indonesia and to evaluate the role of government policies in its implementation. The research method used is descriptive qualitative with a Systematic Literature Review (SLR) approach, based on secondary data such as government policy documents, scientific articles, and relevant reports. Data were collected through document studies from 24 reference journals and analyzed to understand the phenomenon of Blue Accounting and its contribution to sustainable economic transformation. The findings indicate that Blue Accounting can significantly contribute to sustainable marine resource management through improved transparency, accountability, and integration of environmental information into financial reporting. Supportive government policies and information technology implementation are key factors in the successful adoption of Blue Accounting. This research provides insights for policymakers and practitioners in developing sustainable Blue Economy strategies in Indonesia.